Moderasi Beragama dalam Islam di Indonesia - Ghafur, Ghafur; Abdul, Octa (Lembaga Yasin AlSys, 2024)
Indonesia is a unique country with its diversity in terms of ethnicity, race, customs, traditions, culture, language, beliefs and beliefs that can blend together in the ideology of Pancasila. Islam as a religion of rahmatan lil-alamin emphasizes the principle of moderation in all aspects of life, including religion. Religious moderation in Islam reflects balance, simplicity, and middleness in living a spiritual life. The aim of writing this work is to review the concept and practice of religious moderation in Islam. The systematics of writing this paper uses the Library Research or Literature Review method, which has a research focus on books, journals and magazines related to the studies raised in the paper. The implementation of religious moderation in Islam is a fundamental principle in living daily life in accordance with the Islamic teachings of rahmatan lil-alamin. Moderation, which is reflected in the concepts of Wasatiyyah (middleness) and Tawazun (balance), namely placing Muslims on the middle path, preventing them from extreme attitudes and fanaticism. In worship, social relations, economics, education, health and lifestyle, the implementation of religious moderation has a profound positive impact. An attitude of tolerance, balance between this world and the hereafter, and sustainability in carrying out religious and social obligations are the core of religious moderation. In facing the challenges of the times, such as unbalanced media influence, changes in social values, and lack of understanding of Islamic teachings, the implementation of religious moderation is becoming increasingly important. Strengthening religious literacy, dialogue between religious communities, and the active role of ulama and community leaders are solutions in maintaining the principle of moderation.